Nickel chloride interferences on zinc and cobalt in graphite furnace atomic absorption spectrometry using a dual cavity platform - Akman, S.; Döner, G. (Elsevier BV, 1995)
The interference mechanisms of nickel chloride in the determination of cobalt and zinc by graphite furnace atomic absorption spectrometry were investigated using a dual cavity platform. This platform, which has two separate cavities instead of one, allows interferences in the gas phase and in the condensed phase to be differentiated by pipetting the analyte and the interferent onto the separate locations as necessary. The interference mechanism of nickel chloride is found to depend upon the pyrolysis temperature. In the presence of excess nickel chloride, analyte chlorides are formed both in the condensed phase and by reaction between analyte species and HCl(g) generated by the hydrolysis of nickel chloride. The analyte chlorides are then lost during pyrolysis or at the very beginning of the atomization step. At low pyrolysis temperatures, where nickel chloride is not significantly hydrolysed, the drop in sensitivity can be attributed to the expulsion of the analyte species together with rapidly expanding decomposition products of nickel chloride, and/or to gas-phase reaction between analyte atoms and chlorine in the atomization step.